Pola Degradasi Hemiselulosa Rumput Rawa Lokal (Sumatera Selatan) pada Kerbau Rawa secara In Sacco - Armina Fariani; G. Muslim; A.S. Nurdin; A.N.T. Pratama; A. Sonia (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Fariani A, Muslim G, Nurdin AS, Pratama ANT, Sonia A. 2020. In sacco local swamp grass hemiselulose degradation pattern on swamp buffalo (South Sumatra). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Studies on the value of swamp forage digestion have been widely conducted, but information about the pattern and rate of degradation of swamp forage is still low. The study aims to evaluate the pattern of hemicellulose degradation of swamp grass in swamp buffalo in Sacco. The study was conducted using Complete Random Design with six treatments and three replications as follows: Rumput Bento Rayap (RBR), Rumput Kumpai Minyak (RKM), Rumput Kumpai Tembaga (RKT), Rumput Kumpai Padi (RKP), Rumput Sendayan (RSN) dan Rumput Purun Tikus (RPT). The observed parameter is the pattern of hemicellulose degradation of swamp grass. The results showed different degradation patterns in six types of swamp grass (p<0.05). Fraction A, Rumput Bento Rayap has the highest score (38.60%) compared to other treatments, and a fraction, b was founded in Rumput Kumpai Padi (19.93 %). Meanwhile, the highest fraction c value was founded in Rumput Sendayan (0.35 %hours) but is no different when compared to Rumput Purun Tikus (0.32 %hours). The highest total digestibility value at incubation period 6 – 48 hours (P-value) was founded in the treatment of Rumput Purun Tikus (333.06 %). Based on the results of this study can be concluded that Rumput Purun tikus has the best digestibility value compared to the other six types of swamp grass.